Trategi Pencegahan Cyberbullying: Studi Persepsi Mahasiswa tentang Normalisasi Cyberbullying di Media Sosial - Suhadah, Suhadah; Khotimah, Husnul; Adawiyah, Rabiatul; Suswandi, Suswandi; Dwi Wulandari, Enza; Andika, Angga; Fahdil, Fahdil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore the perceptions of students of Universitas Muhammadiyah Mataram towards the normalization of cyberbullying on social media and to formulate appropriate prevention strategies. This study uses a qualitative approach with a descriptive exploratory design. The results of the study indicate that the normalization of cyberbullying occurs due to the lack of social regulation in digital media, low digital literacy, and negative influences from the family and school environment. Students identified forms of cyberbullying such as body shaming, public insults, and hurtful jokes as part of interactions that are often considered